Floral organ development goes live. (23rd January 2020) - Rambaud-Lavigne, Léa; Hay, Angela
Abstract : Quantitative live-cell imaging is an exciting approach to study floral organs. In this review, we highlight recent advances using this approach to understand floral organ initiation and cell fate acquisition. Abstract: The chance to watch floral organs develop live is not to be missed! Here, we outline reasons why quantitative, live-cell imaging is an important approach to study floral morphogenesis, and provide a basic workflow of how to get started. We highlight key advances in morphodynamics of lateral organ development, and discuss recent work that uses live confocal imaging to address the regulation of floral organ number, its robustness, and patterning mechanisms that exploit stochasticity.